2014
DOI: 10.4236/ojmm.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sectional Study of Skin Carriage and Enterotoxigenicity of Staphylococcus aureus among Food Handlers

Abstract: The prevalence of enterotoxigenic Staphylococcus aureus was investigated among 200 participants working in three different food processing plants in Egypt. Using skin swabs, 75 (38%) of the 200 tested persons were positive for the presence of S. aureus. Of the S. aureus positive persons, 28 (14%) harboured S. aureus produced staphylococcal enterotoxins. The serotypes of these enterotoxins were enterotoxin A (68%), enterotoxin B (36%), enterotoxin C (46%) and enterotoxin D (18%). Some of these isolates produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…Of the total collected samples, 43% of nose samples and 15% of hand samples were found to be carrying S. aureus (Table 1). Our results on nasal and skin carriage of S. aureus by food handler's (43% and 15%, respectively) were in agreement to the previous report by Loeto et al [23] and El-Shenawy et al [24] demonstrating the prevalence of S. aureus among food handlers of Botswana and Egypt, respectively. Carriage rates of S. aureus reported by several investigators differ and these variations may be due to the ecological differences of the studied population.…”
Section: Prevalence Of Toxigenic Mrsasupporting
confidence: 82%
“…Of the total collected samples, 43% of nose samples and 15% of hand samples were found to be carrying S. aureus (Table 1). Our results on nasal and skin carriage of S. aureus by food handler's (43% and 15%, respectively) were in agreement to the previous report by Loeto et al [23] and El-Shenawy et al [24] demonstrating the prevalence of S. aureus among food handlers of Botswana and Egypt, respectively. Carriage rates of S. aureus reported by several investigators differ and these variations may be due to the ecological differences of the studied population.…”
Section: Prevalence Of Toxigenic Mrsasupporting
confidence: 82%
“…Throughout the four airlines catering the study failed to find free hands from the Escherichia coli the percentage of contaminated hand washes reach (54.5%) this can be attributed to either in efficient hand washing or post hand washing contamination similar study support the results of this study by Lues (2006) reported that Escherichia coli was isolated from (78%) of the hand samples. The result of this study found that Staphylococcus aureus were present in (72.7%) on the hands of food handlers samples throughout the four studied catering these findings should be a serious concern for management, as this indicates that food handlers do not comply with hand hygiene during food handling , these pathogens may be transmitted to food contaminating it and causing food-borne illnesses, in study done by Hatakka (2000) also support this study finding reported that the prevalence of Staphylococcus aureus among finish flight catering employees (9%) according to hand sampling, other studies had a similar result by El-Shenawy et al (2014) reported infection rate with Staphylococcus aureus (38%)) and (11%) by Abdel-Rahman et al (2014) . This result showed an association with the absence of hands washing facilities in the studied catering and the presence of the microbial contamination of hands, in general, the microbial contamination on hands of food handlers appeared higher the presence of Escherichia coli and Staphylococcus aureus on hands is an indication of poor hand hygiene, as identified during the observation phase of the data collection.…”
Section: Discussionsupporting
confidence: 79%
“…The relation between duration of work and MRSA in the present study was not significant. Similar results were obtained by [18,19]. Though, a study done by Eveillard et al (2004) on hospital employees showed that the duration of work increases the risk of MRSA rate [20].…”
Section: Duration Of Worksupporting
confidence: 87%
“…It is proven by many researchers that the favorable prevalence is among workers who have contacts with foods that allow S. aureus to grow. However, the differences in results might be attributed to different factors like, educational level, cleaning behavior, the hygiene equipment and the work environment [19,25]. The highest proportion of MRSA was observed among cooks (36.9%), followed by waiters and kitchen assistants.…”
Section: Job Type and Mrsamentioning
confidence: 95%